2011
DOI: 10.2217/whe.11.74
|View full text |Cite
|
Sign up to set email alerts
|

Use of Bone Turnover Markers in Clinical Osteoporosis Assessment in Women: Current Issues and Future Options

Abstract: Monitoring bone turnover of the adult and aging skeleton is essential for optimal treatment of bone metabolic diseases, such as postmenopausal osteoporosis. Diagnosis of osteoporosis is based solely on dual-emission x-ray absorptiometry-based measurements of bone mineral density. However, within the last 20 years, biochemical markers of bone turnover have been implemented to a larger degree, and especially within the field of drug development. Numerous clinical studies have underscored that the markers have pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 112 publications
0
13
0
Order By: Relevance
“…The reduction of oestrogen levels is related to the development of postmenopausal osteoporosis in female populations 5, 21. This study simulates menopause by removing the ovaries in female C57BL/6 mice, resulting in postmenopausal osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reduction of oestrogen levels is related to the development of postmenopausal osteoporosis in female populations 5, 21. This study simulates menopause by removing the ovaries in female C57BL/6 mice, resulting in postmenopausal osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to simulate the pharmacologic intervention after diagnosis of osteoporosis in clinical practice, we added tectorigenin into the medium after the appearance of osteoclasts to evaluate its therapeutic effect. Tartrate-resistant acid phosphatase staining showed less osteoclasts in tectorigenin-treated groups, which indicated that tectorigenin treatment had a therapeutic effect on RANKL-induced osteoclast differentiation in vitro.The reduction of oestrogen levels is related to the development of postmenopausal osteoporosis in female populations 5,21. This study simulates menopause by removing the ovaries in female C57BL/6 mice, resulting in postmenopausal osteoporosis.…”
mentioning
confidence: 99%
“…Furthermore, as illustrated by the β -CTX-I example, numerous parameters need to be investigated in detail in order to validate the relevance of a potential marker [80], and whether this approach or other approaches, that is, mass spectrometry-based analyses of CSF and/or plasma samples, will end up providing a fluid biomarker with a broader application remains to be seen. …”
Section: Conclusion and Challengesmentioning
confidence: 99%
“…The use of this marker in the bone field has illustrated many of the benefits and a few of the challenges of this class of biomarkers [11]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition it has been shown to respond to various anti-resorptive treatments, and to have predictive value for treatment efficacy on bone mineral density (BMD) [11]. Hence the β-CTX-I biomarker fits into all the BIPED categories [16].…”
Section: Introductionmentioning
confidence: 99%